ASYNAPSIS 1 ensures crossover fidelity in polyploid wheat by promoting homologous recombination and suppressing non-homologous recombination - Di Dio, Chiara; Serra, Heïdi; Sourdille, Pierre; Higgins, James D. (Frontiers in Plant Science, 2023)
During meiosis, the chromosome axes and synaptonemal complex mediate chromosome pairing and homologous recombination to maintain genomic stability and accurate chromosome segregation. In plants, ASYNAPSIS 1 (ASY1) is a key component of the chromosome axis that promotes inter-homolog recombination, synapsis and crossover formation. Here, the function of ASY1 has been cytologically characterized in a series of hypomorphic wheat mutants. In tetraploid wheat, asy1 hypomorphic mutants experience a reduction in chiasmata (crossovers) in a dosage-specific manner, resulting in failure to maintain crossover (CO) assurance. In mutants with only one functional copy of ASY1, distal chiasmata are maintained at the expense of proximal and interstitial chiasmata, indicating that ASY1 is required to promote chiasma formation away from the chromosome ends. Meiotic prophase I progression is delayed in asy1 hypomorphic mutants and is arrested in asy1 null mutants. In both tetraploid and hexaploid wheat, single asy1 mutants exhibit a high degree of ectopic recombination between multiple chromosomes at metaphase I. To explore the nature of the ectopic recombination, Triticum turgidum asy1b-2 was crossed with wheat-wild relative Aegilops variabilis. Homoeologous chiasmata increased 3.75-fold in Ttasy1b-2/Ae. variabilis compared to wild type/Ae. variabilis, indicating that ASY1 suppresses chiasma formation between divergent, but related chromosomes. These data suggest that ASY1 promotes recombination along the chromosome arms of homologous chromosomes whilst suppressing recombination between non-homologous chromosomes. Therefore, asy1 mutants could be utilized to increase recombination between wheat wild relatives and elite varieties for expediting introgression of important agronomic traits.